2013
DOI: 10.2807/1560-7917.es2013.18.50.20659
|View full text |Cite
|
Sign up to set email alerts
|

Middle East Respiratory Syndrome (MERS) coronavirus seroprevalence in domestic livestock in Saudi Arabia, 2010 to 2013

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
218
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(234 citation statements)
references
References 9 publications
12
218
0
4
Order By: Relevance
“…There is growing evidence that the dromedary camel is a host species for the MERS-CoV and that camels play an important role in the transmission to humans [2,3]. The first evidence of the implication of dromedary camels in transmission was the detection of high rates of MERS-CoV antibodies in dromedary camels on the Arabian Peninsula [4,5].…”
Section: Zoonotic Transmissionmentioning
confidence: 99%
“…There is growing evidence that the dromedary camel is a host species for the MERS-CoV and that camels play an important role in the transmission to humans [2,3]. The first evidence of the implication of dromedary camels in transmission was the detection of high rates of MERS-CoV antibodies in dromedary camels on the Arabian Peninsula [4,5].…”
Section: Zoonotic Transmissionmentioning
confidence: 99%
“…In August 2013, dromedary camels (Camelus dromedarius) were implicated for the first time as a possible source for human infection on the basis of the presence of MERS-CoV neutralizing antibodies in dromedaries from Oman and the Canary Islands of Spain (2). Since then, the presence of MERS-CoV antibodies in dromedaries has been reported in Jordan (3), Egypt (4,5), the United Arab Emirates (6,7), and Saudi Arabia (8,9). In October 2013, analysis of an outbreak associated with 1 barn in Qatar (10) found dromedaries and humans to be infected with nearly identical strains of MERS-CoV.…”
mentioning
confidence: 99%
“…In August 2013, for the first time, dromedary camels were implicated as a possible source of virus causing human infection because of the presences of MERS-CoV specific neutralizing antibodies in dromedary camels from Oman and other countries in the Arabian Peninsula and North Africa (15)(16)(17)(18)(19). An analysis of an outbreak of MERS-CoV infection in humans in Qatar in October 2013 found that dromedary camels and humans were infected with a nearly identical strain of MERS-CoV (18). Further studies from Saudi Arabia supported the hypothesis that dromedary camels act as reservoirs of MERS-CoV (17,19).…”
Section: Sources Of Infection and Transmission Routesmentioning
confidence: 99%
“…There is growing evidences that the dromedary camel is host species for MERS-CoV and plays an important role in the transmission of the viruses to human (15)(16)(17)(18)(19)(20). In August 2013, for the first time, dromedary camels were implicated as a possible source of virus causing human infection because of the presences of MERS-CoV specific neutralizing antibodies in dromedary camels from Oman and other countries in the Arabian Peninsula and North Africa (15)(16)(17)(18)(19). An analysis of an outbreak of MERS-CoV infection in humans in Qatar in October 2013 found that dromedary camels and humans were infected with a nearly identical strain of MERS-CoV (18).…”
Section: Sources Of Infection and Transmission Routesmentioning
confidence: 99%